Parasites and Infection: Strategies to Control, Diagnose, and Treat Parasitic Diseases - Erica S. Martins-Duarte (Microorganisms)
This Special Issue features thirteen publications on the basic biology, genetics, novel diagnostic tools and treatments, control strategies, disease epidemiology, and pathogenesis of medically significant protozoan and helminth parasites [...]